Becoming More Grounded: The Enduring Appeal of Ancient Pilgrimage for the Contemporary Seeker - King, Yehudit (Religions, 2024)
This article builds on a previous essay and arises from research carried out between the summer of 2018 and the spring of 2020 among pilgrims who had participated in the Camino de Santiago in northwestern Spain and St Patrick’s Purgatory on Lough Derg in the northwest of Ireland. Research focused on embodied experience in relation to pilgrim motivation, groundedness and the enduring power of sacred travel as ritual. Convergent considerations about psychology, theology and pilgrimage studies were deployed as lenses of analysis of the pilgrims’ experience. The findings brought clarity in relation to pilgrims’ motivations and the subsequent satiation experienced as they became more grounded in relation to the physical rituals of the pilgrimage. The experience of full-blooded, fleshy embodiment, the analysis suggests, has considerable psychological dividend and is, the discussion argues, of theological significance, particularly from the perspective of Incarnation. As pilgrimage scholars have noted, a refreshing outcome of 21st Century research is the way in which it has been lifted out of the ‘narrow fields of religious or medieval studies’ and yet the analysis of this study suggests that we not dismiss the enduring possibility of religious quest as a still traceable element in the experience of contemporary pilgrimage.